The Spirit of 1848: German Immigrants. Labor Conflict, and the Coming of the Civil War - Jentz, John B. (Labour / Le Travail, 1993)
The article reviews the book, "The Spirit of 1848: German Immigrants, Labor Conflict, and the Coming of the Civil War," by Bruce Levine.
Keywords: BOOKS -- Reviews; LEVINE, Bruce; MIGRANT labor; Nonfiction; SPIRIT of 1848: German Immigrants, Labor Conflict & the Coming of the Civil War, The (Book)